Scoping Review: Dampak Kesehatan dan Sosial dari Pernikahan Dini pada Perempuan di Negara Berkembang - Hanik Khairun Nisa; Prima Dhewi Ratikaningtyas; Sri Ratna Ningsih (Jurnal Kesehatan Manarang, 2022)
Early marriage is a form of violence and violations of children's rights, this is because the practice of early marriage occurs at the age of <18 years which triggers violence such as sexual violence. Early marriage occurs in many developing countries such as Africa, India, Bangladesh, Nigeria, Nepal and Indonesia. This study aims to examine the previous literature to collect data on â€œThe Impact of Early Marriage on Women from Health and Social Aspects in Developing Countriesâ€. This study employed a scoping review method with the Arskey and O'Malley framework. A systematic review was carried out using online databases, namely PubMed, Willey, ProQuest, and using Gray Literature with predetermined keywords, then the articles were filtered based on inclusion and exclusion criteria. There were 25 articles that met the criteria. This study identified that early marriage had a serious impact on women's health and social life such as the occurrence of sexually transmitted diseases, cervical cancer, preeclampsia and complications during pregnancy and childbirth, as well as mental health disorders such as stress and anxiety. The impact of the social aspects found in the literature review was the existence of gender discrimination, dropping out of school, domestic violence, and low autonomy in decision making. In addition, in the review of the article, it was found that the factors that influence the practice of early marriage experienced by women were education, economy, culture, parents and marriage by accident (MBA). The existence of complications during pregnancy and childbirth is the impact of early marriage that is often experienced by women. In addition, gender discrimination is often felt by women who marry at the age of <18 years in various developing countries.